Energy Generation Intensity (EGI) of Solar Updraft Tower (SUT) Power Plants Relative to CSP Plants and PV Power Plants Using the New Energy Simulator “Aladdin” - Osama A. Marzouk (Energies, 2024)
The current investigation provides information about solar updraft tower power plants, SUTPPs (also called solar chimney power plants, SCPPs), which form a unique method of solar-powered electricity production through a ducted wind turbine driven by induced airflow as a result of solar heating. The investigation is conducted using numerical modeling via the system-level simulation tool Aladdin (developed and released freely by the Institute for Future Intelligence, IFI) for solar energy systems, wind energy systems, or the built environment. The Aladdin energy simulator is first evaluated here by comparison with published experimental and numerical results corresponding to the historical 50 kW prototype SUTPP that was successfully tested in Manzanares (Spain) between 1982 and 1989. This prototype has a height of about 195 m for the chimney (the updraft tower) and a radius of about 122 m for the solar heat absorber (the solar air collector or the greenhouse). Next, various climate and performance characteristics are investigated and contrasted for nine different locations around the world with a similar latitude of 24°, which is within the sunbelt, assuming that the same Manzanares SUTPP prototype geometry is employed in these locations. These nine locations are Muscat (Oman), Al Jawf (Libya), Riyadh (Saudi Arabia), Karachi (Pakistan), Ahmedabad (India), Havana (Cuba), Culiacán (Mexico), Dhaka (Bangladesh), and Baise (China). The energy generation intensity (EGI) for the Manzanares-type solar updraft tower power plant in these nine examined locations was between 0.93 kWh/m2 per year (in Baise) and 2.28 kWh/m2 per year (in Muscat). Also, Muscat had the smallest seasonality index (maximum-to-minimum monthly electric output) of 1.90, while Baise had the largest seasonality index of 4.48. It was found that the main limitation of the overall SUTPP energy conversion efficiency is the chimney efficiency (the process of accelerating the air after entering the chimney). This study concludes that solar updraft towers (SUTs) cannot compete with existing mature and modular renewable energy alternatives, particularly photovoltaic (PV) panels, if the aimed use is commercial utility-scale electricity generation. Instead, SUTs may become attractive and achievable if viewed as hybrid-use projects by serving primarily as a large-scale greenhouse area for agricultural applications while secondarily allowing energy harvesting by generating clean (emissions-free) electricity from the incoming solar radiation heat.